2008
DOI: 10.1002/pssc.200778573
|View full text |Cite
|
Sign up to set email alerts
|

Chemical lift‐off of GaN epitaxial films grown on c‐sapphire substrates with CrN buffer layers

Abstract: GaN epitaxial films are grown on c‐plane sapphire substrates with CrN buffer. The GaN layers show high crystalline quality and smooth surface morphology without being cracked. Selective etching of CrN buffer is performed by wet etching using conventional Cr metal etchant, which results in success ful lift‐off of GaN thick layers. We confirm that the crystalline quality of GaN does not change through the etching process. These results indicate that the chemical lift‐off process using CrN buffer is promising for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 7 publications
(5 reference statements)
0
14
0
2
Order By: Relevance
“…It should be mentioned that sapphire substrates thinner than 100 μm cannot be recommended because of handling problems. Details of the growth procedures of GaN on CrN/sapphire are described elsewhere [6]. Briefly, a metallic Cr layer pre-deposited on sapphire substrates was nitrided under NH 3 ambient in our HVPE system to form a CrN layer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be mentioned that sapphire substrates thinner than 100 μm cannot be recommended because of handling problems. Details of the growth procedures of GaN on CrN/sapphire are described elsewhere [6]. Briefly, a metallic Cr layer pre-deposited on sapphire substrates was nitrided under NH 3 ambient in our HVPE system to form a CrN layer.…”
Section: Methodsmentioning
confidence: 99%
“…If we use thin sapphire substrate (say 150 μm thick) in stead of conventional 450 μm-thick sapphire substrate, the sapphire substrate will be fractured during cooling down after growth by tensile thermal stress. Regarding the buffer layer which can be chemically etched, we have already demonstrated that CrN can serve as a buffer layer for the growth of high-quality GaN layers [5] and that CrN can be etched [6]. Hence the CrN buffer has been applied to chemical-lift-off of thick GaN layers [6] and to the fabrication of vertical LEDs [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Отделение тонкой пленки GaN с выращенной на ней вертикальной приборной структурой от изолирующей ростовой сапфировой подложки позволяет перенести структуру на проводящую подложку с высокой тепло-проводностью [2,3]. При изготовлении приборов на осно-ве GaN часто используется метод лазерного отделения пленки GaN от сапфировой подложки (Laser Lift-Off) с использованием ультрафиолетового (УФ) лазера [4,5].…”
Section: Introductionunclassified
“…Лазерное сканирование сапфировой подложки приводило к термической диссо-циации GaN на интерфейсе GaN/сапфир и отделению пленки GaN от сапфира. Пороговая плотность энергии лазерного излучения, при которой начиналась диссоциация n-GaN, составила 1.6 ± 0.5 Дж/см 2 . Изучено распределение механических напряжений и поверхностная морфология пленок GaN и сапфировых подложек до и после лазерного отделения методами рамановской спектроскопии, атомно-силовой микроскопии и растровой электронной микроскопии.…”
unclassified